Hybrid Systems: Computation and Control 10th International Workshop, HSCC 2007, Pisa, Italy, April 3-5, 2007, Proceedings - Bemporad, Alberto; Buttazzo, Giorgio C.; Bicchi, Antonio (Theoretical Computer Science and General Issues, 2007)
This book constitutes the refereed proceedings of the 10th International Conference on Hybrid Systems: Computation and Control, HSCC 2007, held in Pisa, Italy in April 2007. The 44 revised full papers and 39 revised short papers presented together with the abstracts of 3 keynote talks were carefully reviewed and selected from 167 submissions. Among the topics addressed are models of heterogeneous systems, computability and complexity issues, real-time computing and control, embedded and resource-aware control, control and estimation over wireless networks, tools for analysis, verification, control, and design, programming languages support and implementation, applications, including automotive, communication networks, avionics, energy systems, transportation networks, biology and other sciences, manufacturing, and robotics.